Indirect DNA readout on the protein side: coupling between histidine protonation, global structural cooperativity, dynamics, and DNA binding of the human papillomavirus type 16 E2C domain - Eliseo, Tommaso (2009)
DNA sequence recognition by the homodimeric C-terminal domain of the human papillomavirus type 16 E2 protein (E2C) is known to involve both direct readout and DNA-dependent indirect readout mechanisms, while protein-dependent indirect readout has been deduced but not directly observed. We have investigated coupling between specific DNA binding and the dynamics of the unusual E2C fold, using pH as an external variable. Nuclear magnetic resonance and isothermal titration calorimetry show that pH titration of His318 in the complex interface and His288 in the core of the domain is coupled to both binding and the dynamics of the beta-barrel core of E2C, with a tradeoff between dimer stability and function. Specific DNA binding is, in turn, coupled to the slow dynamics and amide hydrogen exchange in the entire beta-barrel, reaching residues far apart from the DNA recognition elements but not affecting the two helices of each monomer. The changes are largest in the dimerization interface, suggesting that the E2C beta-barrel acts as a hinge that regulates the relative position of the DNA recognition helices. In conclusion, the cooperative dynamics of the human papillomavirus type 16 E2C beta-barrel is coupled to sequence recognition in a protein-dependent indirect readout mechanism. The patterns of residue substitution in genital papillomaviruses support the importance of the protonation states of His288 and His318 and suggest that protein-dependent indirect readout and histidine pH titration may regulate DNA binding in the cell